Management of colonic complications of type IV Ehlers–Danlos syndrome: a systematic review and evidence‐based management strategy. (31st July 2019) - Speake, D.; Dvorkin, L.; Vaizey, C. J.; Carlson, G. L.
Abstract: Aim: Type IV Ehlers Danlos Syndrome (EDS) is a connective tissue disorder affecting approximately 1 per 100, 000‐200, 000 people. Life expectancy is reduced secondary to spontaneous vascular rupture or colonic perforation. Surgery carries significant morbidity and mortality. While strategies to manage colonic perforation include primary repair with or without a defunctioning stoma, Hartmann's procedure, total abdominal colectomy with end ileostomy and ileorectal anastomosis, evidence is contradictory and has not previously been evaluated in order to form a treatment strategy. We aim to review the published literature and identify outcome data relating to operative management of colonic perforation in type IV EDS. Methods: Pubmed, EM‐BASE, Cochrane library and Google Scholar were searched with the following details: Ehlers Danlos Syndrome AND colonic surgery. The main outcome measure was re‐perforation rates following colonic surgery on patients with type IV EDS. If the nature of surgery and follow up were reported, data were recorded in a SPSS database according to PRISMA guidelines. Results: One hundred and nine operations have been described in 51 patients in 44 case series. There were 26 visceral re‐perforations, 2 affecting the small intestine and 24 colonic. Survival analysis favoured total abdominal colectomy compared with operations where the colon was left in situ . Conclusions: Total abdominal colectomy with end ileostomy or ileorectal anastomosis are the safest strategies after colonic perforation in type IV EDS. Anastomotic leak rates are high. End colostomy is high risk for colonic re‐perforation and anastomotic leak rates are extremely high. Restoration of colonic continuity should be avoided.